The Partial Averaging of Fuzzy Differential Inclusions on Finite Interval - Andrej V. Plotnikov; Tatyana A. Komleva (International Journal of Differential Equations)
The substantiation of a possibility of application of partial averaging method on finite interval for differential inclusions with the fuzzy right-hand side with a small parameter is considered.